Antibacterial activity of diacetylcurcumin against Staphylococcus aureus results in decreased biofilm and cellular adhesion - Orlandi Sardi, Janaina de Cassia; Polaquini, Carlos Roberto [UNESP]; Freires, Irlan Almeida; Carvalho Galvao, Livia Camara de; Lazarini, Josy Goldoni; Torrezan, Guilherme Silva [UNESP]; Regasini, Luis Octavio [UNESP]; Rosalen, Pedro Luiz (Microbiology Soc, 2017)
Purpose. Staphylococcus aureus infections have contributed to the global healthcare burden, particularly with regard to hospital-acquired meticillin-resistant S. aureus (MRSA) infections. Methodology. This study describes the antibacterial activity of diacetylcurcumin (DAC) against meticillin-susceptible S. aureus/MRSA biofilm formation, survival, metabolic activity and structure; its ability to prevent bacterial adhesion to human cells; and toxicity in Galleria mellonella larvae. Results. DAC showed excellent antibacterial activity, with MIC ranging between 17.3 and 34.6 mu mol l(-1), and minimum bactericidal concentration ranging between 69 and 277 mu mol l(-1). It significantly reduced bacterial biofilm survival - by 22-63% (at MIC, 10 x MIC or 100 x MIC) as compared to the 25-42% reduction by vancomycin (P<0.0001) - and severely affected biofilm cell structures, leading to damaged architecture and the formation of amorphous cell clusters. Treatment with DAC (MIC/4) decreased bacterial adhesion to HaCaT keratinocytes from 1 to 5 h (P<0.0001). Finally, DAC demonstrated low toxicity in G. mellonella at its effective anti-biofilm concentrations. Conclusion. These findings open new avenues for the study of this curcumin derivative as an excellent prototype with anti-MRSA activity.
Keywords: diacetylcurcumin; curcumin; Staphylococcus aureus; anti-adhesion; antibiofilm; toxicity